Penggunaan dan Makna Adverbia ‘Shikkari’ dalam Polisemi Bahasa Jepang Tinjauan Semantik - Wahyu Cipta Widiastika, I Wayan (Humanis; Vol 26 No 3 (2022), 2022)
This article discusses the use and meaning of the adverb 'shikkari' in everyday Japanese polysemy. The data in this article were obtained from spoken data used by native Japanese speakers. The method used in this article is descriptive method. To obtain valid data, a field study was conducted directly to dig up the required information through the interview method and assisted with note-taking techniques. The data were analyzed using Pateda's theory of contextual meaning (2010: 116). From the data that has been collected, the adverb 'shikkari' in Japanese polysemy has different meanings depending on the context in which it is used. From the results of the analysis, in general the adverb 'shikkari' means (1) a strong/sturdy foundation and building structure, (2) a strong body, soul and personality, (3) a clear goal and a strong memory, (4) something trustworthy and reliable, (5) do something hard in terms of work/learning, and (6) actions and behaviour (good, sharp, and healthy).